THE SOCIAL IMPORTANCE AND EDUCATIONAL ROLE OF PRESERVING NATIONAL MUSICAL HERITAGE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This study explores the significance of safeguarding national musical heritage, emphasizing its educational and social relevance, particularly in nurturing the cultural consciousness and personal maturity of youth. National musical art is presented not only as a cultural expression but also as a critical social institution influencing the ethical and emotional development of individuals. Special attention is given to the preservation of classical traditions such as maqom, performance styles, and master-apprentice pedagogical systems. The article underscores the necessity of transmitting these elements to future generations in their authentic forms. It is argued that national music plays a transformative role in shaping spiritual values, aesthetic sensibilities, and cultural identity. The pedagogical approach rooted in oral transmission is discussed as an effective methodology in musical education. Overall, the article advocates for a comprehensive and respectful engagement with traditional music to enrich the educational experience of young learners.